M-Mode Echocardiographic Studies in Healthy Cats - Brahmwar, Aarush; Hase, Pankaj; Gaikwad, Rajiv; Galdhar, Chandrakant; Pawalkar, Dhananjay; Patil, Manjusha (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
M-mode echocardiography is a non-invasive and indispensible tool for the quantitative evaluation of the heart. Due to domestic cats’  sedentary lifestyles, it has been difficult to diagnose heart disorders in cats since they frequently manifest and exhibit cardiac affections  in novel ways. In order to help in the diagnosis of heart disorders in cats, this study was carried out to create baseline reference data  in cats (n=12) with mean age of 3.43±1.28 years, weighing 4.43 ±0.45 kg, irrespective of breed and gender, having mean heart rate of  173.67±10.34 beats/min that are bred and fed in India. The M-mode parameters studied with their mean ±SD values were Interventricular  septal thickness at diastole (IVSd, 3.50±1.15 mm) and systole (IVSs, 5.65±1.13 mm), Left ventricular internal diameter at diastole (LVIDd,  13.48±2.00 mm) and systole (LVIDs, 7.35±1.15 mm), Left ventricular posterior wall thickness at diastole (LVPWd, 4.53±0.74 mm) and  systole (LVPWs, 6.58±0.82 mm), Ejection fraction (EF, 80.55±2.58%), Fractional shortening (FS, 45.50±2.69%), Left atrium (LA, 1.06±0.17  cm), Aorta (AO, 0.86±0.13 cm), LA/Ao ratio 1.25±0.09 and E point to septal separation (EPSS, 1.21±0.51 mm). These baseline values  established will facilitate comparison and precise interpretation by the clinician.
Keywords: Echocardiography; Feline; M-mode echocardiography; Reference values